Photoreceptor-Specific Temporal Contrast Sensitivities in RP1L1-Associated Occult Macular Dystrophy - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan; Kühlewein, Laura; Kempf, Melanie; Ott, Saskia; Stingl, Krunoslav; Stingl, Katarina (Investigative Ophthalmology & Visual Science, 2023)
Purpose: The purpose of this study was to compare L-, M-, S-cone-, and rod-driven temporal contrast sensitivities (tCS) in patients with RP1L1-associated autosomal-dominant occult macular dystrophy (OMD), and to investigate how photoreceptor degeneration determines which post-receptoral channels dominate perception. Methods: Photoreceptor isolating stimuli were created with the silent substitution technique. Photoreceptor-selective tCS deviations (D L-cone/M-cone/S-cone/Rod) were obtained as a function of temporal frequency with identical retinal adaptation, by subtracting tCS from age-corrected normal values. A linear-mixed effects model was used for analysis. Results: Eleven genetically confirmed patients were included (7 women, 5 men; age = 52.27 ± 14.44 years). Overall, L- and M-cone-driven sensitivity deviations (DL-cone and DM-cone) were more negative than DS-cone; DRod was normal at frequencies between 8 and 12 Hz in all subjects. Rod-driven tCS functions allowed identification of two subgroups of patients: one with band-pass properties and one with low-pass properties, suggesting dominance of different post-receptoral filters. The same filtering properties were observed in L-cone-driven tCS functions. Furthermore, the two subgroups also differed in clinical parameters (spherical equivalent, BCVA, perimetry, and ocular coherence tomography (OCT) reflectivity of the ellipsoid zone relative to the RPE). Conclusions: OMD was characterized predominantly by deterioration of L- and M-cone-cone driven function in the perifovea. Rod-driven functions were normal. Differences in the photoreceptor signals were further modified by postreceptoral filters.
CRIS-Team Scopus Importer:2023-07-07